Keeping innovative projects aligned with strategy - Man, Adrianus Pieter de 1967-; Plotnikova, Anna; Hoeksema, Ludwig H. (MIT Sloan Management Review, 2024)
Companies that encourage teams to move fast and experiment must take care that new initiatives get sufficient oversight and remain aligned with the overall corporate strategy. Some have established a portfolio team made up of top executives to monitor and adjust the mix of fledgling projects that might fall outside of existing corporate structures like R&D or business lines.
Reprint #65339
Keywords: Strategic planning; New products; Planification stratégique